Comparative analysis and forecast of dynamics of main macroeconomic indicators of households economic activities of Poland and Ukraine - Zhuk, Mykola (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The purpose of the paper is to compare and analize the differences in households economic activities systems in Poland and Ukraine and also to forecast the dynamics of the main indicators of households economic activities in both countries. The author has developed two VAR-models ofhouseholds economic activities systems of Poland and Ukraine. The impulse response of the main indicators of households economic activities systems in both countries to shocks in all variables of models was investigated. Inverse roots of autoregressive characteristic polynomials constructed on the basis of the VAR-models were analized. The dynamics of household consumption expenditures was forecasted to show the quality of forecast power of developed models.
Keywords: household; households economic activities system; macroeconometric model; impulse response; forecast